PERAN DAN LEGALITAS WALI HAKIM DALAM PERNIKAHAN MUALAF: Prespektif Hukum Keluarga Islam - Annisa Afroo, Fakhriyah; Vratiwi, Septiana; Febri Wialdi, Putri; Slipilia, Intan (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2025)
Marriage is a sacred institution in Islam that governs the lawful relationship between men and women based on sharia. One of the essential requirements for a valid marriage involving a woman is the presence of a legal guardian (wali). Problems arise when a female convert to Islam (muallafah) has no Muslim guardian. This article aims to analyze the role and legal status of the wali hakim (judge guardian) in the marriage of converts according to Islamic Family Law in Indonesia. The research applies a qualitative approach using library research methods with sources including the Qur'an, hadith, Islamic jurisprudence, national regulations, and academic literature. The findings indicate that the wali hakim has both sharia and legal authority to act as a marriage guardian in specific circumstances, such as the absence or disqualification of a biological guardian. The function of the wali hakim is carried out by an official from the Office of Religious Affairs (KUA) based on provisions from the Compilation of Islamic Law (KHI) and Regulation of the Minister of Religious Affairs No. 20 of 2019. Therefore, the presence of the wali hakim is a valid legal solution that ensures the legitimacy of a convert’s marriage and protects their religious rights within the framework of Islamic and national law.